Biocontrol Efficacy of the Vishniacozyma Victoriae in Semi‑Commercial Assays for the Control of Postharvest Fungal Diseases of Organic Pears - Gorordo, María Florencia (2022)
Vishniacozyma victoriae NPCC 1263 was selected for this work because of the active antagonistic effect over several fungi in postharvest organic pears. Yeast biomass production was carried out in a 15 L stirred-tank bioreactor with 12 L of working volume at 20 °C and 300 rpm and 0.64 vvm of aeration. The selected production medium was based on cheese whey powder and salts. The present study aims to evaluate the possibility of using an inexpensive growth substrate for production of added value products (yeast biomass), this innovation also requires evaluate biocontrol efficacy of yeast against fungal diseases of pears in semi-commercial assays. The yeast biomass was collected, cold stored for 60 days (Treatment 1) and 15 days (Treatment 2) and sprayed on the pears in semi-commercial level testing assays. After 180 days of postharvest conservation, significant reduction of fungal infection by Penicillium expansum, Botrytis cinerea and Cladosporium sp. was observed. The Treatment 1 reduced total diseases incidence by 71%, instead Treatment 2 reduced it by 92%. The effect of spray application on the yeast viability with different cold storage was tested. These work provides information on the bench-scale bioreactor yeast production using a new low-cost medium, viability and biocontrol efficacy of Vishniacozyma victoriae in controlling common diseases affecting pears in semi-commercial assays.